LIPID EXTRACT OF GRACILARIA SP. AS AN ANTI-APOPTOTIC CANDIDATE FOR CANCER THERAPY - Isriyanti Affifah; Rahmat Firman Septiyanto; Fida Madayanti Warganegara (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2023)
It has been claimed that an Indonesian seaweed lipid extract possesses antibacterial properties. The mitochondrial pathway reported that a long fatty acid (more than 10 carbon atoms), which is known as the major component in seaweed lipid extract, acts as an apoptotic agent. It has also been claimed that unsaturated fatty acids can prevent apoptosis. on this study, we investigated the role of an Indonesian seaweed lipid extract on the mitochondrial pathway of apoptosis. Lipid isolation was the first step of the study, which was carried out using centrifugation and a chloroform-methanol-phosphate buffer 2:1:0,8. Rotary evaporators were used to separate the lipid extract from its solvent. Dry weight Gracilaria sp. yield extraction was 21,8%. By using several centrifugation techniques in SET buffer (0,25 M Sucrose, 0,5 mmol EDTA, and 10 mmol/L Tris base), pH 7,4, mitochondria were recovered from rat liver. By adding 10% (v/v) lipid extract to a suspension of mitochondria, toxicity testing from the lipid extract was undertaken. By using light microscopy, mitochondrial morphological damage was seen. Gracilaria sp. exhibits strong apoptotic activity.